Technical match characteristics and influence of body anthropometry on playing performance in male elite team handball - Michalsik, L. B.; Madsen, K.; Aagaard, P. (The Journal of Strength and Conditioning Research, 2015)
Modern team handball match-play imposes substantial physical and technical demands on elite players. However, only limited knowledge seems to exist about the specific working requirements in elite team handball. Thus, the purpose of this study was to examine the physical demands imposed on male elite team handball players in relation to playing position and body anthropometry. Based on continuous video recording of individual players during elite team handball match-play (62 tournament games, ~4 players per game), computerized technical match analysis was performed in male elite team handball players along with anthropometric measurements over a 6 season time span. Technical match activities were distributed in 6 major types of playing actions (shots, breakthroughs, fast breaks, tackles, technical errors, and defense errors) and further divided into various subcategories (e.g., hard or light tackles, type of shot, claspings, screenings, and blockings). Players showed 36.9 ± 13.1 (group mean ± SD) high-intense technical playing actions per match with a mean total effective playing time of 53.85 ± 5.87 minutes. In offense, each player performed 6.0 ± 5.2 fast breaks, received 34.5 ± 21.3 tackles in total, and performed in defense 3.7 ± 3.5 blockings, 3.9 ± 3.0 claspings, and 5.8 ± 3.6 hard tackles. Wing players (84.5 ± 5.8 kg, 184.9 ± 5.7 cm) were less heavy and smaller (p < 0.001) than backcourt players (94.7 ± 7.1 kg, 191.9 ± 5.4 cm) and pivots (99.4 ± 6.2 kg, 194.8 ± 3.6 cm). In conclusion, modern male elite team handball match-play is characterized by a high number of short-term, high-intense intermittent technical playing actions. Indications of technical fatigue were observed. Physical demands differed between playing positions with wing players performing more fast breaks and less physical confrontations with opponent players than backcourt players and pivots. Body anthropometry seemed to have an important influence on playing performance because it is highly related to playing positions. The present observations suggest that male elite team handball players should implement more position-specific training regimens, while also focusing on anaerobic training and strength training.